Civil inattention—On the sources of relational segregation - Arminen, Ilkka A. T.; Heino, Anna S. M. (Frontiers in Sociology, 2023)
The article employs ethnomethodological conversation analysis (CA) and experimental video analysis to scrutinize the gaze behavior of urban passersby. We operationalize Goffman's concept of civil inattention to make it an empirical research object with defined boundaries. Video analysis enabled measurement of gaze lengths to establish measures for “normal” gazes within civil inattention and to account for their breaches. We also studied the dependence of gazing behavior on the recipient's social appearance by comparing the unmarked condition, the experimenter wearing casual, indistinctive clothes, to marked conditions, the experimenter wearing either a distinct sunhat or an abaya and niqab. The breaches of civil inattention toward marked gaze recipients were 10-fold compared to unmarked recipients. Furthermore, the analysis points out the commonality of hitherto unknown micro gazes and multiple gazes. Together the findings suggest the existence of subconscious monitoring beneath the public social order, which pre-structures interaction order, and indicates that stigmatization is a source for relational segregation.